A Triple Network Connectivity Study of Large-Scale Brain Systems in Cognitively Normal APOE4 Carriers - Wu, Xia; Li, Qing; Yu, Xinyu; Chen, Kewei; Fleisher, Adam S.; Guo, Xiaojuan; Zhang, Jiacai; Reiman, Eric M.; Yao, Li; Li, Rui (Frontiers in Aging Neuroscience, 2016)
The triple network model, consisting of the central executive network, salience network and default mode network, has been recently employed to understand dysfunction in core networks across various disorders. Here we used the triple network model to investigate the large-scale brain networks in cognitively normal APOE4 carriers who are at risk of Alzheimer’s disease (AD). To explore the functional connectivity for each of the three networks and the effective connectivity among them, we evaluated 17 cognitively normal individuals with a family history of AD and at least one copy of the apolipoprotein e4 (APOE4) allele and compared the findings to those of 12 individuals who did not carry the APOE4 gene or have a family history of AD, using independent component analysis and Bayesian network approach. Our findings indicated altered within-network connectivity that suggests future cognitive decline risk, and preserved between-network connectivity that may support their current preserved cognition in the cognitively normal APOE4 allele carries. The study provides novel sights into our understanding of the risk factors for AD and their influence on the triple network model of major psychopathology.